1990
DOI: 10.1038/345502a0
|View full text |Cite
|
Sign up to set email alerts
|

Major determinants of the specificity of interaction between small nuclear ribonucleoproteins U1A and U2B" and their cognate RNAs

Abstract: The basis of the specificity of interaction of U1 and U2 small nuclear (sn)RNAs and their cognate binding proteins, U1A and U2B'', has been examined. The U1A protein recognizes U1 snRNA on its own, whereas U2B'' binds specifically to U2 snRNA only in the presence of a second protein, U2A'. Exchange of two nucleotides between the two RNAs or of eight amino acids between the two proteins reverses binding specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
304
5
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(327 citation statements)
references
References 31 publications
17
304
5
1
Order By: Relevance
“…One of the least conserved regions in the RNP-CS RBD is the region preceeding RNP1, referred to as loop 3. Amino acids in loop 3 are thought to be important for determining RNA-binding specificity, and this has been shown experimentally for two proteins, the U1-A and U2-B" snRNP proteins (38 obtained. Interestingly, immunopurification and two-dimensional gel analysis indicated that monoclonal antibody 8A6 recognizes hnRNP F, hnRNP H and the lower molecular weight hnRNP E proteins, revealing that, in addition to their similar nucleic acidbinding properties, these proteins share a common epitope ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…One of the least conserved regions in the RNP-CS RBD is the region preceeding RNP1, referred to as loop 3. Amino acids in loop 3 are thought to be important for determining RNA-binding specificity, and this has been shown experimentally for two proteins, the U1-A and U2-B" snRNP proteins (38 obtained. Interestingly, immunopurification and two-dimensional gel analysis indicated that monoclonal antibody 8A6 recognizes hnRNP F, hnRNP H and the lower molecular weight hnRNP E proteins, revealing that, in addition to their similar nucleic acidbinding properties, these proteins share a common epitope ( Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Mutation analysis of the human U2BЉ gene has previously shown which part of the sequence localizes U2BЉ to the nucleus (Scherly et al, 1990;Bentley and Keene, 1991;Kambach and Mattaj, 1994), but not which part of the sequence is responsible for localization to the coiled body. We have shown that fusion of the first N-terminal RNP-80 motif of the potato U2BЉ protein to GFP is sufficient for localization of the fusion protein to the coiled body.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that U2BЉ may not be required for the splicing reaction itself but may have a role in U2 snRNP biogenesis (Mattaj and De Robertis, 1985;Pan and Prives, 1989). The full-length U2BЉ cDNA has been cloned from potato (Simpson et al, 1991) and has been characterized at the molecular level (Simpson et al, 1991, largely by analogy with the human U2BЉ cDNA (Scherly et al, 1990;Bentley and Keene, 1991;Kambach and Mattaj, 1994). The potato U2BЉ protein contains two RNP-80 motifs separated by a central putative nuclear localization signal (NLS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the fact that both differences are at the loop-3 region, which lies at the N-terminal end of RNP-1 P-sheet, is intriguing. Since the loop-3 and RNP-1 sequences of U 1-A and U2-B" have been shown to determine the binding specificity of these proteins (Scherly et al, 1990;Bentley and Keene, 199 l), the optional addition of 5 amino acids to the RBP9 protein in this region and the 13 extra amino acids of efav at the loop-3 region may confer on them different RNA binding specificities or affinities. In addition, the facts that two related fly proteins, elav and rbp9, have a different expression profile-eelav is required for the early embryo neurogenesis whereas rbp9 is expressed only at the late developmental stages-and that a rbp9 cDNA under the efav promoter failed to rescue the embryonic lethal phenotype of elav (K. M. Yao and K. White, personal communication) are consistent with the idea that these two proteins are involved in different functions rather than having synonymous functions in the CNS development.…”
Section: Discussionmentioning
confidence: 99%